FACTORS AFFECTING CASH HOLDING IN TECHNOLOGY COMPANIES - Cliff, Andreas; Yanti , Yanti (International Journal of Application on Economics and Business, 2024)
The purpose of this study was to examine the effect of net working capital [NWC], capital expenditure [CAPEX], growth opportunities [GROWTH], and firm size [SIZE] on cash holding. The research method used is multiple linear regression analysis. The sampling technique used was purposive sampling which resulted in 10 technology companies listed on the IDX. The regression test results show that capital expenditure has a negative and significant effect on cash holding and firm size has a positive and significant effect on cash holding. Meanwhile, net working capital has a positive and insignificant effect on cash holding and growth opportunities have a negative and insignificant effect on cash holding.